Kaempferol activates chloride secretion via the cAMP/PKA signaling pathway and expression of CFTR in T84 cells - Thaweewattanodom, Janjira; Deachapunya, Chatsri; Poonyachoti, Sutthasinee (Frontiers in Pharmacology, 2024)
Kaempferol is a flavonol identified as the most potent activator of chloride (Cl−) secretion among other flavonoids in airway epithelial cells. This study aimed to investigate the cellular mechanisms by which kaempferol stimulates Cl− secretion in the T84 human colon carcinoma cell line by Ussing chambers and voltage clamp technique. Bilateral addition of kaempferol (1–100 µM) increased short-circuit current (Isc) in a concentration-dependent manner. Ion substitution of Cl− or CFTR inhibitors NPPB and glibenclamide or a Na+/K+/2Cl− cotransporter inhibitor bumetanide attenuated kaempferol-induced Isc response. In permeabilized monolayers, selective channel inhibitors CFTRinh-172 and CaCCinh-A01 inhibited kaempferol-induced apical Cl− current (ICl), and K+ blockers BaCl2 and clotrimazole inhibited basolateral K+ current (IKb). The kaempferol-induced ICl showed no additive effects with forskolin or 8cpt-cAMP. The kaempferol-induced ICl was mostly abolished by protein kinase A inhibitor H89, but not by tyrosine kinase inhibitors, AG490 and tyrphostin A23, or tyrosine phosphatase inhibitor vanadate. Treatment with kaempferol for 24 h increased the expression of CFTR protein as determined by the Western blot analysis. These results demonstrated that kaempferol activates Cl− secretion across T84 cells by activating the apical Cl− current and basolateral K+ current. The mechanisms may involve the cAMP/PKA pathway and CFTR expression. Taken together, these findings reveal the beneficial effects of kaempferol to increase fluid secretion which can be used to treat constipation.